2023
DOI: 10.3390/educsci13050476
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Academic Self-Efficacy and Intolerance of Uncertainty on Decisional Procrastination in University Students during the COVID-19 Pandemic

Abstract: Decisional procrastination has been one of the main phenomena analysed in university students, together with self-efficacy, during the COVID-19 pandemic. We examined the roles of academic self-efficacy and intolerance of uncertainty on decisional procrastination in 318 Italian university students. Furthermore, the mediating role of the intolerance of uncertainty on the relationships between academic self-efficacy and decisional procrastination was explored. The Academic Self-Efficacy Scale, the Decisional Proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Additionally, it has been confirmed that the prospective intolerance of uncertainty plays a mediating role in the relationship between self-efficacy (specifically self-engagement and self-oriented decision-making) and decisional procrastination, as outlined in a study by Sagone and Indiana in 2023. The outcome of the multidimensional scaling analysis reveals noteworthy variations in student borrowing and book renewal patterns pre-and post-epidemic.…”
Section: Impact Of Covid-19mentioning
confidence: 68%
“…Additionally, it has been confirmed that the prospective intolerance of uncertainty plays a mediating role in the relationship between self-efficacy (specifically self-engagement and self-oriented decision-making) and decisional procrastination, as outlined in a study by Sagone and Indiana in 2023. The outcome of the multidimensional scaling analysis reveals noteworthy variations in student borrowing and book renewal patterns pre-and post-epidemic.…”
Section: Impact Of Covid-19mentioning
confidence: 68%
“…In educational research, the academic self-efficacy of students has become a focal point of interest. Previous studies have consistently shown a positive association between academic self-efficacy and a range of favorable academic outcomes, including improved academic performance and increased engagement in the learning process ( Multon et al, 1991 ; Honicke and Broadbent, 2016 ; Huang, 2016 ; Sagone and Indiana, 2023 ). Additionally, a robust sense of academic self-efficacy has been recognized as a protective factor against the adverse impacts of academic stressors experienced by students ( Ye et al, 2018 ).…”
Section: Review Of Literaturementioning
confidence: 97%
“…Procrastination in performing tasks and works has various reasons, but usually, students who procrastinate in their tasks lack sufficient cognitive and self-regulation skills, which causes their procrastination in performing their tasks. In other words, procrastination is associated with an illogical cognitive process (Popova & Pronenko, 2023;Qian & Zhao, 2018;Sagone & Indiana, 2023;Saplavska & Jerkunkova, 2018). Behind most procrastinations, there is a task or activity that the individual prefers to avoid as much as possible.…”
Section: Introductionmentioning
confidence: 99%